The Study on Fluorescence Characteristics of Chlorella spp: pH Influence on Culture - P., Retno Wigajatri; Handojo, Andrianto; Kurniawan, Hendrik; Prihantini, N. B. (Makara Journal of Technology, 2003)
The Study on Fluorescence Characteristics of Chlorella spp: pH Influence on Culture. Experiments for measuring the fluorescence characteristics of Chlorella spp. by using high stability and high repetition rate nitrogen laser of energy 5 mJ with pulse duration of 5 ns have been carried out. The results show that for a cell concentration range from 2,625 cells/ml up to 2,769,000 cells/ml, the fluorescence intensities at pada λ = 687 nm have a linear relationship with the cell concentration. It has been also found that for a 7 days old chlorella culture, the pH variation at the starting culture influenced the cell concentration.